Model Pembelajaran Tatalepa Blended Learning di Masa Pandemi Covid-19 untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa - Hidayat, Asep (utile: Jurnal Kependidikan, 2022)
Research, entitled " Application of the Tatalepa Blended Learning Model During the Covid-19 Pandemic to Improve Student Activity and Learning Outcomes in ICT Subjects for Class VII Students of SMPN 1 Bojonggenteng " aims to determine the application of the tetalepa blended learning model in SMPN 1 Bojonggenteng and to improve student learning outcomes by implementing this model. This research is a classroom action research, the subject of this research is class VII as many as 30 students. Student learning outcomes are measured using various instruments. Assessment of student knowledge is carried out using multiple choice test questions, assessment of student skills is measured using portfolio assessment, while assessment of attitudes is measured using observation sheets, self-assessment, and peer assessments. The results showed that student learning outcomes had increased, namely in the initial / pre-cycle activities the average student learning outcomes were 71 with a 50% percentage of completeness increased in cycle 1 with an average learning outcomes of 74 but the percentage of completeness was still at 50%. Then in cycle 2 the average student learning outcomes increased to 80 with a percentage of 90% completeness and student activity increased from 41% in cycle 1 to 83% in cycle 2.In conclusion, students can meet the Minimum Completeness Criteria (KKM) of 75 using the model blended learning